Spatial and Temporal Changes in the Broiler Chicken Cecal and Fecal Microbiomes and Correlations of Bacterial Taxa with Cytokine Gene Expression - Oakley, Brian B.; Kogut, Michael H. (Frontiers in Veterinary Science, 2016)
To better understand the ecology of the poultry gastrointestinal (GI) microbiome and its interactions with the host, we compared GI bacterial communities by sample type (fecal or cecal), time (1, 3, and 6 weeks post-hatch), and experimental pen (1, 2, 3, or 4), and measured cecal mRNA transcription of the cytokines IL18, IL1β, and IL6, IL10, and TGF-β4. The microbiome was characterized by sequencing of 16S rRNA gene amplicons, and cytokine gene expression was measured by a panel of quantitative-PCR assays targeting mRNAs. Significant differences were observed in the microbiome by GI location (fecal versus cecal) and bird age as determined by permutational MANOVA and UniFrac phylogenetic hypothesis tests. At 1 wk post-hatch, bacterial genera significantly over-represented in fecal versus cecal samples included Gallibacterium and Lactobacillus, while the genus Bacteroides was significantly more abundant in the cecum. By 6 wk post-hatch, Clostridium and Caloramator (also a Clostridiales) sequence types had increased significantly in the cecum and Lactobacillus remained over-represented in fecal samples. In the ceca, the relative abundance of sequences classified as Clostridium increased by ca. 10-fold each sampling period from 0.1% at 1 wk, to 1% at 3 wk, and 18% at 6 wk. Increasing community complexity through time were observed in increased taxonomic richness and diversity. IL18 and IL1β significantly (p<0.05, pairwise t-tests) increased to maximum mean expression levels 1.5 fold greater at wk 3 than wk 1, while IL6 significantly decreased to 0.8-fold and 0.5-fold expression at 3 wk and 6 wk post-hatch respectively relative to wk 1. Transcription of pro-inflammatory cytokines was generally negatively correlated with the relative abundance of various members of the phylum Firmicutes and positively correlated with Proteobacteria. Correlations of the microbiome with specific cytokine mRNA transcription highlights the importance of the GI microbiome for bird health and productivity and may be a successful high-throughput strategy to identify bacterial taxa with specific immune-modulatory properties.